Relationship organizational commitment and emotional intelligence with work performance of adult students - Nurul Fatihah Mohamad Nurhadi Chow; Nurul-Azza Abdullah (Penerbit Universiti Kebangsaan Malaysia, 2019)
This study aims to see the relationship between organizational commitment and emotional intelligence with work performance among adult students. Organizational commitment aspect and emotional intelligence are important aspects in affecting the performance of adult students who may be affected by the burden of responsibility. The subjects were selected using the sampling method consisting of 167 students of Distance Learning at a local university. This study uses the four-part survey method that is part of respondent's demographic information, part of organizational commitment using organizational commitment questionnaire (OCQ), emotional intelligence division that uses the Wong and Law Emotional Intelligence Scale (WLEIS) to evaluate emotional intelligence of adult and final student once the section measures work performance using a work performance questionnaire modified by Fatimah Wati Halim and Iran Herman (1977). The findings showed that there were postive relationships and influence between organizational commitment and emotional intelligence on the performance of adult students. The results of this study can be a reference to the institution of study that manages the admission of adult students to make this aspect of emotional intelligence something that needs to be in the adult student and this study is hoped to help organizations where today's students work to improve the organizational commitment aspect among their workers.